Jovens e associações em Moçambique: motivações e dinâmicas actuais [Youths and associations in Mozambique: motivations and current dynamics] - Biza, Adriano Mateus (Saúde e Sociedade, 2009)
O presente artigo é uma reflexão sobre dinâmicas associativas de jovens no Moçambique pós colonial. O objectivo desta reflexão foi identificar e analisar as motivações de engajamento dos jovens nesses agrupamentos. Baseando-se em aproximações empíricas feitas a duas associações de jovens - Associação Aro Juvenil e Associação Positiva Juvenil - a análise demonstra que dinamica associativa de jovens mete em evidência relações complexas entre identidade, contexto, o privado, o público e o afectivo. Embora haja múltiplas motivações, a adesão dos jovens em associações associa trajectórias e expectativas individualizadas. A nível discursivo, a entrada na vida associativa representa uma forma de legitimação sóciopolítica em resposta a um discurso que considera os jovens passivos e pouco intervenientes na solução dos problemas que lhes afecta em particular e à sociedade no geral. A nível das práticas associativas quotidianas, os jovens reintrepretam e dão outro sentido às motivações do seu engajamento: para lá dos objectivos formais, pretensamente desenvolvimentistas, altruistas e humanitários, o associativismo é uma estratégia de vida e de realização de projectos individuais. Criar uma associação e/ou nela aderir pode significar maiores possibilidades de aceder e controlar recursos e capitais diversificados como emprego/profissão, dinheiro, trabalho, poder, reconhecimento e prestigio, formações entre outros que de outra forma não seria possível. en: This article reflects on youth associations dynamics in Postcolonial Mozambique. The aim is to identify and analyze motivations for young people's involvement in such groups. Based on empirical work with two youth associations - namely "Associação Aro Juvenil" and "Associação Positiva Juvenil" - the assessment finds that youth associations dynamics highlights intricate relationships involving identity, context, private, public and affective milieus. Although there are multiple motivations, young people's adherence to associations is combined with individual life stories and expectations. At the discourse level, entrance to the associative life represents a form of socio-political legitimation in response to other narratives that consider young people very passive and less intervening in finding solutions to their own problems, and society's in general. At the level of day-to-day practices, young people re-interpret and give a different sense to their motivations and commitment: beyond formal objectives - arguably development-oriented, altruistic and humanistic - associations are a life strategy for the accomplishment of individual achievements. To create an association and/or take part in one may imply greater possibilities of accessing and controlling diversified resources and capitals, such as a job/occupation, money, work, power, recognition, prestige, and training, among others, which would be otherwise impossible.
Publisher: Saúde e Sociedade
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; citizenship & participation / cidadania e participação; decentralization / descentralização; youth / juventude

Power and Participation in Rural Development: A Case Study from Mozambique - Valderrama, Camilo Eduardo (Institute of Development Studies, University of Sussex, 2009)
This study on power and participation in post-conflict settings analyzes a rural development project in Mandimba District of Northern Mozambique. The purpose is to gain understanding of the dynamics and possibilities of participatory approaches for increasing the influence of previously excluded actors in decision-making processes. The methodology for this study reflects two broad yet intertwined approaches. For the first component, the Mozambique in-depth case study research, I draw on my role as a participant observer as well as other more traditional field research approaches. A variety of qualitative methods were used for the collection of the information, including review of documentary sources, participant observation, key informant and focus group interviews. The initial data collection lasted about eight months in different phases between 1998 and 1999. In Mozambique, but also in subsequent years, my approach drew upon principles of reflective practice, where I learned not only through the study of others, but through reflections on my work as a practitioner in conflict areas being studied. This latter approach was particularly important when triangulating and extending the findings from the Mozambique study to other war-torn settings in which I later worked in Kosovo, Pakistan and Chad and when reviewing documented experiences in participatory processes in Afghanistan and East Timor. A 'power over' and 'actor oriented' approach informed data collection and analysis of the information. The findings show that inclusive participatory approaches may fail if they do not address power. They may sideline power asymmetries and fail to set rules of involvement for actors within the project. In addition, structural and functional factors related to the project frame can enhance or constrain participation. The finding also shows that the inflexibility of the project frame constrains actor engagement in decision-making processes. The theoretical implication of this research calls for an approach to power rooted in the mix of conflict and consensual understanding of power. Practical implications point towards a greater emphasis on 'decision ruling', i.e. setting the 'rules of the game' for decision-making in participatory processes.
Publisher: Falmer : University of Sussex
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mandimba; GP - Niassa; L - english / inglês; citizenship & participation / cidadania e participação; conflict - civil war / conflito - guerra civil; conflict / conflito; power / poder; rural development / desenvolvimento rural